A STUDY OF FREE VIBRATION AND FATIGUE FOR CROSS-PLY CLOSED CYLINDRICAL SHELLS USING GENERAL THIRD SHELL THEORY (GTT) (Journal of Engineering, 2010)
Free vibration solution will be developed for laminated simply supported closed cylindrical shells. This solution is obtained using General Third Shell Theory (G.T.T.). Also the critical in-plane fatigue load is studied and the required equilibrium equations are developed, the effects of tension or compression in-plane load on the natural frequencies are discussed also. The natural frequencies and in-plane fatigue load results are very close to those obtained by other researchers.